Exploring Health-Related Quality of Life and Correlates Among Patients with Type 2 Diabetes Mellitus Attending Primary Health Centers in Aljouf Province, Saudi Arabia: A Multi-Site Cross-Sectional Study - Alsaidan AA; Alshehri AA; Thirunavukkarasu A; Alsaidan OA; Alhassan HH; Morad MH; Alshehari A; Alibrahim A (Risk Management and Healthcare Policy, 2025)
Aseel Awad Alsaidan,1 Abdulmajeed Ali Alshehri,1 Ashokkumar Thirunavukkarasu,1 Omar Awad Alsaidan,2 Hassan H Alhassan,3 Muaid Hashem Morad,4 Abdullah Alshehari,5 Alaa Alibrahim6 1Department of Family and Community Medicine, College of Medicine, Jouf University, Sakaka, Aljouf, Saudi Arabia; 2Department of Pharmaceutics, College of Pharmacy, Jouf University, Sakaka, Aljouf, Saudi Arabia; 3Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, Jouf University, Sakaka, Aljouf, Saudi Arabia; 4Department of Internal Medicine, College of Medicine, Al-Baha university, Al-Baha, Saudi Arabia; 5Department of Quality and Patient Safety, Khamis Mushayte Hospital, Aseer, Saudi Arabia; 6Department of Internal Medicine, College of medicine, Jouf university, Aljouf, Saudi ArabiaCorrespondence: Aseel Awad Alsaidan, Department of Family and Community Medicine, College of Medicine, Jouf University, Sakaka, 72388, Saudi Arabia, Tel +966-506065757, Email aaalsaidan@ju.edu.saPurpose: Type 2 diabetes mellitus (T2DM) impacts various elements of health-related quality of life (HRQoL). However, research on the HRQoL of T2DM patients in primary healthcare settings in Saudi Arabia is limited. Therefore, we aimed to determine the HRQoL and associated factors among patients with T2DM to plan policy-driven interventions and improve patient outcomes.Participants and Methods: We surveyed 390 patients with T2DM attending primary health centers (PHCs) in the Aljouf province of Saudi Arabia. We included Saudi adults (≥ 18 years) diagnosed at least six months before the study and completed at least one follow-up visit at the PHC. In the present cross-sectional study, we used the validated 20-item short-form health survey (SF-20)-Arabic tool to assess different HRQoL domains. We performed Mann–Whitney U and Kruskal–Wallis tests for dichotomous and categorical variables, respectively, in each domain. Finally, a binomial logistic regression analysis was performed to determine the predictors of overall HRQoL.Results: The role functioning domain had the highest mean score (75.7± 19.7), and the lowest scores were in the social functioning (47.9± 20.2) and pain domains (48.9± 21.4). Some characteristics, such as marital status, treatment type, and follow-up adherence, were significantly associated with most domains. HRQoL was significantly higher in male patients (p=0.002, adjusted odds ratio [AOR]=2.66) and those on oral hypoglycemic agents (OHAs; p=0.002, AOR=5.18). Obese patients had a significantly lower HRQoL (p=0.036, AOR=0.058). These factors remained significant after adjusting for age, sex, body mass index, treatment type, and comorbidities in the multivariate analysis.Conclusion: We recommend policy changes that incorporate interventions tailored to improve HRQoL, especially in social functioning and pain domains. Moreover, integrating comprehensive pain management strategies and enhancing patient follow-up within PHCs may improve quality of life, especially for high-risk patients with T2DM.Keywords: diabetes mellitus, primary healthcare, quality of life, T2DM patients, SF-20, pain management